The clinical effectiveness and cost effectiveness of clozapine for inpatients with severe borderline personality disorder (CALMED study): a randomised placebo-controlled trial. (April 2022) - Crawford, Mike J.; Leeson, Verity C.; Evans, Rachel; Barrett, Barbara; McQuaid, Aisling; Cheshire, Jack; Sanatinia, Rahil; Lamph, Gary; Sen, Piyal; Anagnostakis, Katina; Millard, Louise; Qurashi, Inti; et al.
Background: Data from case series suggest that clozapine may benefit inpatients with borderline personality disorder (BPD), but randomised trials have not been conducted. Methods: Multicentre, double-blind, placebo-controlled trial. We aimed to recruit 222 inpatients with severe BPD aged 18 or over, who had failed to respond to other antipsychotic medications. We randomly allocated participants on a 1:1 ratio to receive up to 400 mg of clozapine per day or an inert placebo using a remote web-based randomisation service. The primary outcome was total score on the Zanarini Rating scale for Borderline Personality Disorder (ZAN-BPD) at 6 months. Secondary outcomes included self-harm, aggression, resource use and costs, side effects and adverse events. We used a modified intention to treat analysis (mITT) restricted to those who took one or more dose of trial medication, using a general linear model fitted at 6 months adjusted for baseline score, allocation group and site. Results: The study closed early due to poor recruitment and the impact of the COVID-19 pandemic. Of 29 study participants, 24 (83%) were followed up at 6 months, of whom 21 (72%) were included in the mITT analysis. At 6 months, 11 (73%) participants assigned to clozapine and 6 (43%) of those assigned to placebo were still taking trial medication. Adjusted difference in mean total ZAN-BPD score at 6 months was -3.86 (95% Confidence Intervals = -10.04 to 2.32). There were 14 serious adverse events; 6 in the clozapine arm and 8 in the placebo arm of the trial. There was little difference in the cost of care between groups. Interpretation: We recruited insufficient participants to test the primary hypothesis. The study findings highlight problems in conducting placebo-controlled trials of clozapine and in using clozapine for people with BPD, outside specialist inpatient mental health units. Trial registration: ISRCTN18352058.https://doi.org/10.1186/ISRCTN18352058